Rap, periferia e questões de gênero: história e representações - Santos, Joelma de Sales dos (2016)
This research aims to reveal about the world of rap and its representations through the songs produced by men and women. The research focus explores the representations that are built on the rap, the issues addressed in the letters, empowerment and self-esteem of black women through the raps and the representation of women in the letters produced by men. Its purpose is to contribute to a perception of rap without categorizing, besides highlighting the productions of rappers to the universe Hip Hop